Extensibility Analysis of Game Engines for Building Simplified Game Development Interfaces - Souza, Joana Gabriela R. de; Pacheco, Marcos Vinicius C.; Prates, Raquel Oliveira (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2024)
Creating video games requires a multidisciplinary team and specialized tools for graphics and interaction mechanisms. While games are valuable educational tools, game engines are often too complex for non-programmers. Simplified design tools democratize game development for educators. This study aims to support Brazilian elementary school teachers by analyzing game engines for customization possibilities and developing a prototype authoring tool to create digital educational games quickly.